Description of Cultural Factors Related to Comprehensive Knowledge of HIV/AIDS among Women in Nepal - Sigdel, Uddhav (Humanities and Social Sciences Journal, 2022)
This research paper has analyzed the individual and cultural factors related to comprehensive knowledge of HIV transmission. Secondary and primary data are used to identify the individual and cultural factors of comprehensive knowledge of HIV/AIDS among women in Nepal. Secondary source of quantitative data is based on NDHS, 2011 and 2016 whereas qualitative data collected from Nam Nagar of Naalparasi (Susta West) district. The total sample size of NDHS 2011 (N=12674) and 2016 (N=12862) are large and nationally representative. The study reveals that only 20 percent of women have comprehensive knowledge of HIV/AIDS. The individual cultural factor such as native language of women[OR= 3.34 (2.21-5.05) in 2011 and OR= 1.47 (1.01-2.13) in 2016] and ethnicity[OR= 1.90 (0.90-3.96) in 2011 and OR=1.74 (1.10-2.74) in 2016] are the influential factors for comprehensive knowledge of HIV/AIDS. Beside these, socially constructed knowledge of HIV/AIDS has been determining the misconception of HIV transmission. The lower level of comprehensive knowledge is trigger by the cross-cultural context of women in Nepal.